Associations of social cohesion and quality of life with objective and perceived built environments: a latent profile analysis among seniors - Hua, J; Mendoza-Vasconez, AS; Chrisinger, BW; Conway, TL; Todd, M; Adams, MA; Sallis, JF; Cain, KL; Saelens, BE; Frank, LD; King, AC (Oxford University Press, 2020)
Background Healthy aging requires support from local built and social environments. Using latent profile analysis, this study captured the multidimensionality of the built environment and examined relations between objective and perceived built environment profiles, neighborhood social cohesion and quality of life among seniors.